A Multidisciplinary NHS COVID-19 Service to Manage Post-COVID-19 Syndrome in the Community. (April 2021) - Parkin, Amy; Davison, Jennifer; Tarrant, Rachel; Ross, Denise; Halpin, Stephen; Simms, Alex; Salman, Rashad; Sivan, Manoj
The National Institute for Health and Care Excellence (NICE) describe " post COVID-19 syndrome " or "Long COVID" as a set of persistent physical, cognitive and/or psychological symptoms that continue for more than 12 weeks after illness and which are not explained by an alternative diagnosis. These symptoms are experienced not only by patients discharged from hospital but also those in the community who did not require inpatient care. To support the recovery of this group of people, a unique integrated rehabilitation pathway was developed following extensive service evaluations by Leeds Primary Care Services, Leeds Community Healthcare NHS Trust and Leeds Teaching Hospital NHS Trust. The pathway aligns itself to the NHS England "Five-point plan" to embed post-COVID-19 syndrome assessment clinics across England, supporting the comprehensive medical assessment and rehabilitation intervention for patients in the community. The pathway was first of its kind to be set up in the UK and comprises of a three-tier service model (level 1: specialist MDT service, level 2: community therapy teams and level 3: self-management). The MDT service brings together various disciplines with specialist skill sets to provide targeted individualized interventions using a specific core set of outcome measures including C19-YRS (Yorkshire Rehabilitation Scale). Community and primary care teams worldwide need such an integrated multidisciplinary comprehensive model of care to deal with the growing number of cases of post-COVID-19 syndrome effectively and in a timely manner.